Manajemen dan Distribusi Seragam di Pondok Pesantren Anwaha serta Dampaknya terhadap Disiplin dan Identitas Santri: Pengabdian - Syahrani; Fatimah Az Zahra; Halimah; Herliani; Iis Maimunah; Indang Rukayah Laluas; Intan (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The management of uniforms at Pondok Pesantren Anwarul Hasaniyyah (ANWAHA) is an integral part of the disciplinary system and the reinforcement of students' identity. This study discusses three main aspects of uniform management: uniform regulations and standards, distribution and management systems, and their impact on students' discipline and identity. The uniform regulations at ANWAHA are designed to reflect Islamic values and instill the habit of dressing neatly and modestly. The distribution and management system is implemented in a structured manner, covering procurement, distribution, and maintenance processes to ensure uniformity and availability of clothing for all students. Additionally, regular supervision is conducted to ensure compliance with the established rules. The implementation of this uniform management system contributes to shaping students' discipline and strengthening the sense of unity and identity within the pesantren. With strict regulations, an efficient distribution system, and periodic evaluations, uniforms serve not only as formal attire but also as a medium for character education that upholds pesantren values.